Community-acquired Achromobacter xylosoxidans infection presenting as a cavitary lung disease in an immunocompetent patient - Hwang, Chan Hee (Yeungnam Univ J Med, 2019)
Achromobacter xylosoxidans is a gram-negative bacterium that can oxidize xylose. It is commonly found in contaminated soil and water but does not normally infect immunocompetent humans. We report a case of a cavitary lung lesion associated with community-acquired A. xylosoxidans infection, which mimicked pulmonary tuberculosis or lung cancer in an immunocompetent man. The patient was hospitalized due to hemoptysis, and chest computed tomography (CT) revealed a cavitary lesion in the superior segment of the left lower lobe. We performed bronchoscopy and bronchial washing, and subsequent bacterial cultures excluded pulmonary tuberculosis and identified A. xylosoxidans. We performed antibiotic sensitivity testing and treated the patient with a 6-week course of amoxicillin/clavulanate. After 2 months, follow-up chest CT revealed complete resolution of the cavitary lesion.